3-(6-methoxy-2-benzimidazolyl)benzothiazolin-2-imine - Song, CE; Jin, BW; Jeong, JH (INT UNION CRYSTALLOGRAPHY, 1996)
The title compound, C15H12N4OS, was unexpectedly isolated from the reaction of N-[2-(6-methoxy-1H-benzimidazol-2-ylthio)phenyl]thiourea with dicyclohexylcarbodiimide. The compound showed considerable anti-cancer activity in vitro. The benzimidazole and iminobenzothiazoline rings are coplanar via hydrogen bonding between the N atom of the imino group of benzothiazole and the H-N bond of benzimidazole. The whole molecule has a planar structure.